Shocks versus structure: Explaining differences in exchange rate pass-through across countries and time - Kristin Forbes; Ida Hjortsoe; Tsvetelina Nenova (Bank of England, External Monetary Policy Committee Unit, 2017)
We show that exchange rate pass-through to consumer prices varies not only across countries, but also over time. Previous literature has highlighted the role of an economy's "structure" - such as its inflation volatility, inflation rate, use of foreign currency invoicing, and openness - in explaining these variations in pass-through. We use a sample of 26 advanced and emerging economies to show which of these structural variables are significant in explaining not only differences in pass-through across countries, but also over time. The "shocks" leading to exchange rate movements can also explain variations in pass through over time. For example, exchange rate movements caused by monetary policy shocks consistently correspond to significantly higher estimates of pass-through than those caused by demand shocks. The role of "shocks" in driving pass-through over time can be as large as that of structural variables, and even larger for some countries. As a result, forecasts predicting how a given exchange rate movement will impact inflation at a specific point in time should take into account not just an economy's "structure", but also the "shocks".
Keywords: E31; E37; E52; F47; 330; Pass-through; exchange rate; price level; inflation; monetary policy